An Analysis of Sustainable Website Designs by Indian Universities - N. Elangovan; E. Sundaravel; L. Ganesh; Eduart Wolok (Universitas Pasundan, 2021)
This study assesses the level of sustainability found in Indian university websites. The study compares the sustainability of 868 websites of universities across India using the URL https://ecograder.com/, which provides a consolidated score on how “green” each website is. Various parameters have been tabulated and statistically analyzed. The research findings demonstrate that most Indian university websites rank far below the sustainability levels expected based on contemporary technological and environmental concerns. Though the websites’ sustainability scores can be easily determined, this study goes on to provide consolidated values and helps benchmark website sustainability. Insights of the study reveal an urgent need for Indian universities to create sustainable websites and set an example for other sustainable initiatives. The study uses a particular tool to calculate the university websites’ consolidated sustainability scores. Other individual tools may be used for an in-depth measure of each sustainability parameter. The study shows that universities exhibit sustainability issues, and their websites are a prime example. Being a fertile ground for sustainability principles and having adequate knowledge of technology, universities need to follow sustainability principles in every aspect and support the industry in creating a greener environment.